DEVELOPMENT OF SCIENCE E-COMICS FOR CLASS VIII JUNIOR HIGH SCHOOL - Dehan Nilvani Gusti; Khairil Arif; Arief Muttaqiin; Yurnetti Yurnetti (SEMESTA: Journal of Science Education and Teaching, 2023)
This research is based on problems in science learning, namely students' lack of interest in reading. One way to increase students' reading interest is by using creative, innovative and interactive learning media. Therefore, this research was carried out by developing a product in the form of a Science E-Comic on the theme, let's get to know the human respiratory and excretory organ systems. This research aims to determine the validity, practicality and effectiveness of products in the form of Science E-Comics on the theme, let's get to know the human respiratory and excretory organ systems. The type of research used is Research and Development (R&D) or development research using the ADDIE model which consists of 5 stages, namely Analyze, design, development, Implementation, and evaluation. Considering the limited time and costs, this research was limited to the implementation stage. The results of the IPA E-Comics validity score of 0.89 are in the very valid category. The practicality of IPA E-Comics obtained an average score of 0.94, which is in the very high category. The effectiveness of IPA E-Comics obtained a fairly large N-Gain score, namely 0.70, which is included in the high category. Based on the research results obtained, it can be concluded that Science E-Comics are declared very valid, very practical and effective in increasing students' reading interest in science learning.